Mammal-rich diet associated with reproductive success of Saker Falcons in Mongolia - Batbayar Bold; Batbayar Galtbalt; Batmunkh Davaasuren; Gankhuyag Purev-Ochir; Amarkhuu Gungaa; Amarsaikhan Saruul; Sarangerel Ichinkhorloo; Ariunzul Lkhagvajav; Nyambayar Batbayar; Yuke Zhang; Zhenzhen Lin; Andrew Dixon; et al. (Avian Research)
Understanding how diet influences the breeding success of Saker Falcons (Falco cherrug) is key to assessing the role of food supply in population dynamics and informing conservation strategies. Through pellet analysis, we evaluated the influence of small mammal prey—present in 95% of pellets—on the reproductive performance of the sakers. In Mongolia, three species comprised 95% of the identified small mammals: Mongolian Gerbil (Meriones unguiculatus, 39%), Brandt's Vole (Lasiopodomys brandtii, 49%) and Daurian Pika (Ochotona dauurica, 7%). We found a strong positive association between the proportion of small mammals in the diet and key breeding parameters of sakers. Clutch size, fledged brood sizes, and nest success all increased with a mammal-rich diet. Earlier laying was also linked to higher small mammal intake and was independently associated with improved breeding outcomes. These findings highlight a critical role of small mammal prey in shaping the reproductive success of sakers. Conserving and restoring grassland habitats that support abundant prey populations is essential for sustaining saker populations and achieving long-term conservation goals.